Audialny wymiar grozy we wczesnej prozie Jakuba Małeckiego - Marek Kurkiewicz (Zagadnienia Rodzajów Literackich, 2025)
A horror story, a genre whose primary role is to instill fear in its audience, uses a variety of methods to achieve its goal. One of these is the skillful building of a mood using the acoustic plane. The following article is an attempt to show the role of (broadly understood) sound in the process of inducing fear in the reader of a horror story, using the example of the first two books by contemporary Polish prose writer Jakub Małecki (Błędy; Przemytnik cudu). The article also refers to the reflections of sound theorist and practitioner David TooP: as well as to the findings of other researchers (Brzostek, Carroll, Marak, Misiak, Regiewicz et al.), who deal with sound on the one hand and horror on the other, it is shown how the writer uses stereotypical ways of provoking fear in his prose (e.g. creaking doors, mysterious moans, howling wails), proposing also original solutions (e.g. an extended motif of eavesdropping). The realm of this type of sound proves to be an attractive platform for building extreme emotions in these publications. Silence and quiet, the sounds of nature and civilization, and all somatic sounds play a similar role, allowing Małecki’s early prose to be read through the prism of somato-aesthetics. The analysis of the selected texts shows that the hitherto existing hierarchy of the senses, favouring sight as the one through which we perceive the world most fully, is not always justified, as hearing plays an equally important role in a horror story. Sometimes the sound overtakes the image, provokes visions or frightens us with something we cannot see, something we only imagine.